Impaired vitamin D signaling is associated with frequent development of renal cell tumor in end-stage kidney disease - Docs, Janos; Banyai, Daniel; Flasko, Tibor; Szanto, Arpad; Kovacs, Gyula (Anticancer research, 2020)
Background/Aim: End-stage kidney disease is characterized by chronic inflammation and frequent development of cancer. The level of circulating vitamin D is generally low in patients with end-stage renal disease (ESRD). Experimental studies have implicated the role of dysfunctional vitamin D metabolism in tumorigenesis. Patients and Methods: We analyzed the expression of vitamin D receptor (VDR), cytochrome P450 family 27 subfamily B member 1 (CYP27B1) and cytochrome P450 family 24 subfamily A member 1 (CYP24A1), the key genes involved in vitamin D signaling, in kidneys from patients with ESRD, tissue microarrays containing ESRD-associated renal cell tumors, as well as in their precursor lesions by immunohistochemistry. Results: Kidneys from patients with ESRD showed strong structural rearrangement with only few tubules and epithelial cell groups embedded in fibrotic-inflammatory stroma. Only an estimated 1-3% of the epithelial cells showed positive staining with antibodies to VDR, CYP27B1 and CYP24A1, which contrasted with the 100%, 40-50% and 40-50% of positively stained cells, respectively, found in normal kidneys. Down-regulation of the vitamin D signaling proteins was found in patients with renal cancer, with the exception of tumors and their precursors occurring exclusively in ESRD. Conclusion: The significantly reduced activity of CYP27B1 in kidney from patients with ESRD explains the low level of circulating vitamin D. We suggest that the lack of anti-tumorigenic effect of vitamin D is a crucial factor in the frequent development of unique types of renal cell cancer in in patients with ESRD.
Gesehen am 04.01.2021